Performance Analysis of VSAT (Very Small Aperture Terminal) Dynamic Single Channel per Carrier - Mahardhika, Muhammad Ilham; Hudiono, Hudiono; Rakhmania, Amalia Eka (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
This paper presents a performance analysis of Dynamic Single Channel per Carrier (dSCPC) technology in Very Small Aperture Terminal (VSAT) systems, focusing on bandwidth efficiency and link quality. Through field measurements at the Telkomsat HUB Surabaya, the study compares the bandwidth utilization of VSAT dSCPC against conventional VSAT IP for the VSAT Colo Surabaya terminal. The analysis employs link budget calculations to evaluate the signal-to-noise ratio (Eₛ/N₀). Measurement results show an average Eₛ/N₀ of 12.05 dB, closely matching the calculated value of 12.002 dB, with a negligible difference of 0.068 dB. The study demonstrates that the dSCPC system achieves a 35% reduction in bandwidth consumption compared to the IP-based system while maintaining superior link margin and more stable resource allocation for terminals with low traffic demand. These findings confirm that dSCPC offers a more efficient satellite bandwidth management solution, optimizing resource utilization without compromising link quality.